A4IP Flagship Event 2024 - Navigating risk and reward in agrifood-tech innovation: The power of multilateralism - CGIAR Accelerate for Impact Platform (2024)
A4IP Flagship Event 2024 - Navigating Risk and Reward in Agrifood-tech Innovation: The Power of Multilateralism. Joined by policymakers, industry experts, scientists, investors, academics and private sector representatives, proceedings focused on how international cooperation and multilateral frameworks can play a critical role in mitigating risks and investor hesitancy in agrifood-tech innovation development and deployment. In-depth discussions explored how governments, international organizations, and the private sector can pool resources, share knowledge, and co-invest to support the growth of solutions that yield tangible rewards for farmers, investors, and societies.